2016
DOI: 10.1177/1932202x16656572
|View full text |Cite
|
Sign up to set email alerts
|

Understanding How Teachers Listen in a Reading Enrichment Program

Abstract: Asking questions that invite students to access advanced thinking skills during classroom discourse is a key strategy for challenging and supporting high-ability middle school readers. This critical teaching practice requires careful teacher listening. However, empirical research around teachers’ listening orientations, or how teachers listen, is sparse. We investigated five middle school reading teachers’ listening orientations as they conducted differentiated reading conferences as part of their first year i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…One could argue that an evaluative listening orientation would be the type of listening teachers exhibit during IRE discourse patterns, while student-oriented listening or interpretive listening would be more common in dialogic discourse exchanges. Gilson and Little (2016) found that the teachers primarily listened to students with an interpretive listening orientation regardless of reading level, which was not surprising given the constructivist nature of this orientation. However, one might have expected stronger patterns of student-oriented listening when teachers asked the students, including gifted readers, higher level questions.…”
Section: Background Literaturementioning
confidence: 73%
See 4 more Smart Citations
“…One could argue that an evaluative listening orientation would be the type of listening teachers exhibit during IRE discourse patterns, while student-oriented listening or interpretive listening would be more common in dialogic discourse exchanges. Gilson and Little (2016) found that the teachers primarily listened to students with an interpretive listening orientation regardless of reading level, which was not surprising given the constructivist nature of this orientation. However, one might have expected stronger patterns of student-oriented listening when teachers asked the students, including gifted readers, higher level questions.…”
Section: Background Literaturementioning
confidence: 73%
“…This student-centered approach to listening aligns with the student-centered nature of dialogic discourse and gifted pedagogy. For example, in a qualitative study of how six reading and ELA middle school teachers listened to students at different reading abilities (i.e., struggling, average, and high ability) while implementing the SEM-R (Reis et al, 2005), Gilson and Little (2016) found that teachers exhibited and self-reported three different listening orientations or combinations thereof, including student-oriented, interpretive, and evaluative listening. Student-oriented listening involved teachers listening more openly to students, responding without preconceived ideas of an answer to a question, and sharing the ownership of leading the discourse with students.…”
Section: Background Literaturementioning
confidence: 99%
See 3 more Smart Citations